2021
DOI: 10.3390/antibiotics10121503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antimicrobial Properties of Bee Venom Extracts and Melittins of Honey Bees

Abstract: Bee venom (BV), or apitoxin, is a complex substance produced by a gland in the abdominal cavity of bees. The main component of BV is melittin, which is a largely studied substance due to its biological properties. To date, the most well-known bee venom and melittin are derived from domesticated honey bees, while venom and melittin derived from wild honey bees have been under-investigated. Hence, this study primarily reports the antimicrobial activities of bee venom and synthetic melittin derived from four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
2
8
1
Order By: Relevance
“…On the other hand, the MIC values for S. aureus were higher than what was demonstrated 30,31 . Similarly, the MIC values of AmBV were 15.625 µg mLG 1 for E. coli ATCC8739 and 7.8 µg mLG 1 for both S. marcescens AUH 98 and S. mutans ATCC 25175 which was much lower than the previously reported MIC values 9,[32][33][34][35] .…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, the MIC values for S. aureus were higher than what was demonstrated 30,31 . Similarly, the MIC values of AmBV were 15.625 µg mLG 1 for E. coli ATCC8739 and 7.8 µg mLG 1 for both S. marcescens AUH 98 and S. mutans ATCC 25175 which was much lower than the previously reported MIC values 9,[32][33][34][35] .…”
Section: Discussioncontrasting
confidence: 57%
“…Bee venom is secreted by bees to protect their colonies (Orsolic 2012 ; Maitip et al 2021 ). It is a mixture of proteins including melittin and peptides that exhibit various pharmacological activities (Lin and Hsieh 2020 ; Guha et al 2021 ; Maitip et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bee venom is secreted by bees to protect their colonies (Orsolic 2012 ; Maitip et al 2021 ). It is a mixture of proteins including melittin and peptides that exhibit various pharmacological activities (Lin and Hsieh 2020 ; Guha et al 2021 ; Maitip et al 2021 ). Melittin, which is composed of 26 amino acids, is known to have antibacterial, anticancer, and anti-inflammatory effects and is being actively used in oriental medicine clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…For S. aureus , as the concentration of the venom fraction increased, bacterial growth was affected. Interestingly, the results of other studies of the antibacterial activity of the crude venom showed highly variable MICs against E. coli and for S. aureus [ 56 ], including also demonstrating the inhibitory effect through a viability assay at a temperature of 25 °C against E. coli and P. putida , causing membrane permeability and loss of ATP, showing no effect against P. fluorescens [ 57 ], as well as the crude bee venom extract in a region of Egypt significantly inhibited the growth of E. coli ATCC8739 and S. aureus ATCC 6538P [ 58 ], in addition, the action of crude bee venom from Iran demonstrated inhibition through the Kirby–Bauer method against E. coli and S. aureus , but not against P. aeruginosa [ 59 ].…”
Section: Discussionmentioning
confidence: 99%